Involved in something (involucrado en algo): denial and stigmatization in Mexico’s “war on drugs” - Moon, Claire (2020)
This article responds empirically to the question posed by Stan Cohen about “why, when faced by knowledge of others’ suffering and pain—particularly the suffering and pain resulting from what are called ‘human rights violations’—does ‘reaction’ so often take the form of denial, avoidance, passivity, indifference, rationalisation or collusion?”. Our context is Mexico's “war on drugs.” Since 2006 this “war” has claimed the lives of around 240,000 Mexican citizens and disappeared around 60,000 others. Perpetrators include organized criminal gangs and state security services. Violence is pervasive and widely reported. Most people are at risk. Our study is based on qualitative interviews and focus groups involving 68 “ordinary Mexicans” living in five different Mexican cities which have varying levels of violence. It investigates participant proximity to the victims and the psychological defense mechanisms they deploy to cope with proximity to the violence. We found that 62 of our participants knew, directly or indirectly, one or more people who had been affected. We also found one dominant rationalization (defense mechanism) for the violence: that the victims were “involved in something” (drugs or organized crime) and therefore “deserved their fate.” This echoes prevailing state discourses about the violence. We argue that the discourse of “involved” is a discourse of denial that plays three prominent roles in a highly violent society in which almost no‐one is immune: it masks state violence, stigmatizes the victims, and sanctions bystander passivity. As such, we show how official and individual denial converge, live, and reproduce, and play a powerful role in the perpetuation of violence